ARGUMENTATION AND TEACHER TRAINING: CURRICULAR AND DIDACTIC TENSIONS IN HIGHER EDUCATION - Figueroa-Vargas, Andrea (2023)
This paper tackles the curricular and didactic tensions observed in the integration and development of argumentation in higher education. The objective of the study carried out in a Chilean university is to identify the didactic, pedagogical and curricular conditions for classroom implementation in the development of argumentative skills in teacher training. The research is based on qualitative approach study, of exploratory design and ascribed to a case study. Focus groups with managers and professors of an early childhood education program were used to carry out a qualitative, exploratory, and case study. The research method of analysis is content operationalized through thematic coding instrumented by the Atlas.ti software. The main results of the research reveal student tensions concerned with the following: entry abilities to higher education, the formulated argumentative structures, the use of evidence and vocabulary in oral and written argumentation. Thus, the main didactic and curricular tensions focus on the treatment of the content of argumentation, the teaching-learning methodologies, the development of cognitive skills through argumentation in the curriculum, and the assessment experiences, yielding particular and focalized instances in teacher training.